2017
DOI: 10.1039/c7ra09250d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GaxZn1−xO nanorods on the photoelectric properties of n-ZnO nanorods/p-GaN heterojunction light-emitting diodes

Abstract: A Ga-doped ZnO nanorod array has been synthesized on a p-GaN/Al2O3 substrate by a hydrothermal method at low temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…14,15 Conversely, Li et al observed no effect on the c-lattice parameter and a decrease in the mean diameter of ZnO NWs. 16 The pH value has not been reported in those three papers. In contrast, Pineda-Hernańdez et al and Saravanakumar et al investigated the spontaneous growth of ZnO nanostructures by CBD at a given pH of 12 following the addition of NaOH.…”
Section: ■ Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…14,15 Conversely, Li et al observed no effect on the c-lattice parameter and a decrease in the mean diameter of ZnO NWs. 16 The pH value has not been reported in those three papers. In contrast, Pineda-Hernańdez et al and Saravanakumar et al investigated the spontaneous growth of ZnO nanostructures by CBD at a given pH of 12 following the addition of NaOH.…”
Section: ■ Introductionmentioning
confidence: 91%
“…In particular, the doping efficiency of Ga into ZnO is much larger than its Al counterpart because the ionic radius of Ga 3+ is closer to the Zn 2+ radius than the Al 3+ radius, opening the way for higher doping levels in ZnO . The evolution of the structural morphology of ZnO NWs grown by CBD, when Ga­(NO 3 ) 3 is used as a chemical additive in the chemical bath, has been reported. However, some of the findings are in apparent discrepancy because the critical parameters including the pH and Ga­(NO 3 ) 3 concentration in the chemical bath as well as the Ga content into the ZnO NWs have not been measured systematically, nor varied on a broad range, nor combined with theoretical thermodynamic simulations. Recently, Lim et al and Park et al showed a decrease in the c -lattice parameter of ZnO NWs and an increase in their mean diameter when the Ga­(NO 3 ) 3 concentration in the chemical bath was increased. , Conversely, Li et al observed no effect on the c -lattice parameter and a decrease in the mean diameter of ZnO NWs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12,13 However, in virtue of the deep acceptor impurity states, low solubility dopants and the self-compensation effect, the intrinsically n-type semiconductor ZnO is difficult to manufacture with a p–n homo-junction architecture for many electronic and optical devices. 14 Thus far, additional p-type substrate materials, for instance, Si, 15 Cu 2 O, 16 GaN, 17 graphene, 18 NiO, 7 B-doped diamond film (BDD) 19–22 and organic materials, 23 have been exploited as the candidate to replace p-type ZnO semiconductors for the fabrication of pn heterojunctions. Among them, the B-doped diamond film (bandgap 5.47 eV) is appropriate as a high-temperature p-type conductive material.…”
Section: Introductionmentioning
confidence: 99%
“…Cu 2 O, 16 GaN, 17 graphene, 18 NiO, 7 B-doped diamond lm (BDD) [19][20][21][22] and organic materials, 23 have been exploited as the candidate to replace p-type ZnO semiconductors for the fabrication of pn heterojunctions. Among them, the B-doped diamond lm (bandgap 5.47 eV) is appropriate as a hightemperature p-type conductive material.…”
mentioning
confidence: 99%